METHOD DEVELOPMENT AND VALIDATION FOR THE ESTIMATION OF DAPAGLIFLOZIN IN MARKETED FORMULATION BY HPLC - Shreya Pandey; Manoj Kumari More; Dr. Udit Narain Soni (The Bioscan, 2025)
Background: Dapagliflozin, a selective sodium-glucose co-transporter-2 (SGLT2) inhibitor, is widely used in the management of type 2 diabetes mellitus (T2DM). For ensuring therapeutic efficacy and safety, reliable analytical methods are required for its estimation in pharmaceutical formulations. Objective: The present study aimed to develop and validate a simple, precise, accurate, and cost-effective reverse-phase high-performance liquid chromatography (RP-HPLC) method for the estimation of dapagliflozin in marketed tablet formulations, in accordance with ICH Q2(R1) guidelines. Methods: Method development was carried out by testing various mobile phase combinations. Methanol and acetonitrile (50:50 v/v) was optimized as the mobile phase, with a flow rate of 1.0 mL/min. The detection wavelength was selected appropriately after scanning. The method was validated for linearity, accuracy, precision, limit of detection (LOD), limit of quantification (LOQ), and assay. Results: The method showed excellent linearity in the concentration range of 5–25 μg/mL with correlation coefficient (r²) of 0.999. Recovery studies at 80%, 100%, and 120% levels indicated accuracy within 98.14–98.80%. Precision results, including repeatability and intermediate precision, were within acceptable limits with %RSD <2%. LOD and LOQ were found to be 0.15 μg/mL and 0.45 μg/mL, respectively. Assay of marketed formulation revealed 99.50% of the labeled claim with low variability. Conclusion: The developed RP-HPLC method is simple, accurate, precise, and sensitive, making it suitable for routine quality control analysis of dapagliflozin in bulk and marketed formulations.